Identification and Analyses of Genes Differentially Expressed During Grain Filling in Indica Rice (Oryza Sativa L.) Variety Mr 84 - Wong, Yick Ching (2006)

(untitled)
Rice is one of the major crops in Malaysia. It has been a staple food of the Malaysian community for many decades. Continued growth of Malaysian population put additional pressure on local rice production to meet the demand of the consumption. Rice grain filling is a critical factor that directly affects the local rice production. This preliminary study was carried out to identify genes that are putatively involved in the grain filling of rice by using cDNA subtraction. Four subtracted cDNA libraries were constructed from three different pools of RNA (samples A, B and C) during the reproductive and ripening phase of rice. A total of 2366 clones were obtained from these four subtracted cDNA libraries and 384 clones were sequenced. In sample A (panicle initiation), most of the sequenced cDNA were putatively involved in cell wall structure and metabolism (38 %) e.g. pollen allergen (subtraction 1). The number of putative genes involved in metabolism (9 %) and storage protein (3 %) was low in this library (subtraction 1). The genes that were differentially expressed in heading to milk stage (sample B) were mainly involved in metabolism (28 %, subtraction 3). Most of the genes that were differentially expressed in sample C (milk stage to maturation) were putative storage proteins (61 %) e.g. glutelins and prolamins, and the genes that were putatively involved in metabolism (10 %) decreased compared to subtraction 3. This reflected that metabolic activities in panicles significantly reduced and most of the activities in grain were involved in reserving food towards the end of the grain filling. To understand the grain filling process during rice growth stages, ADP-glucose pyrophosphorylase which is the rate-limiting enzyme in starch biosynthesis was studied. The cDNA for the 3’ region of ADP-glucose pyrophosphorylase small subunit (Adp3’-2) (which showed 97 % identity to ADP-glucose pyrophosphorylase small subunit from japonica cultivar) was isolated. It was preferentially expressed in milk and dough stage of grain development. Southern analysis showed that Adp3’-2 may be a single copy gene in the rice genome. In addition, bZIP protein which has a regulatory role in several plant developmental processes including seed storage has also been cloned. The cDNA for the 3’ region of bZIP protein was also isolated. No signal was detected in Northern analysis attributed to its low expression in panicle, and the Southern analysis also suggested that 3’ Reb-2 may be a single copy gene in the rice genome